Unexpected mosaic distribution of two hybridizing sibling lineages in the teleplanically dispersing snail Stramonita haemastoma suggests unusual postglacial redistribution or cryptic invasion. Issue 21 (25th September 2017) - El Ayari, Tahani; Trigui El Menif, Najoua; Saavedra, Carlos; Cordero, David; Viard, Frédérique; Bierne, Nicolas
Abstract: Molecular approaches have proven efficient to identify cryptic lineages within single taxonomic entities. Sometimes these cryptic lineages maybe previously unreported or unknown invasive taxa. The genetic structure of the marine gastropod Stramonita haemastoma has been examined in the Western Mediterranean and North‐Eastern Atlantic populations with mtDNA COI sequences and three newly developed microsatellite markers. We identified two cryptic lineages, differentially fixed for alternative mtDNA COI haplogroups and significantly differentiated at microsatellite loci. The mosaic distribution of the two lineages is unusual for a warm‐temperate marine invertebrate with a teleplanic larval stage. The Atlantic lineage was unexpectedly observed as a patch enclosed in the north of the Western Mediterranean Sea between eastern Spain and the French Riviera, and the Mediterranean lineage was found in Macronesian Islands. Although cyto‐nuclear disequilibrium is globally maintained, asymmetric introgression occurs in the Spanish region where the two lineages co‐occur in a hybrid zone. A first interpretation of our results is mito‐nuclear discordance in a stable postglacial hybrid zone. Under this hypothesis, though, the location of genetic discontinuities would be unusual among planktonic dispersers. An alternative interpretation is that the Atlantic lineage, also found in Senegal and Venezuela, has been introduced by human activities in the Mediterranean area and is introgressing Mediterranean genes during its propagation, as theoretically expected. This second hypothesis would add an additional example to the growing list of cryptic marine invasions revealed by molecular studies. Abstract : The Atlantic lineage of a marine snail was found enclosed in the Mediterranean Sea between eastern Spain and the French Riviera. The unusual position of the hybrid zone and asymmetric introgression suggests cryptic invasion.